Nuclear Nuevo México : Colonialism and the Effects of the Nuclear Industrial Complex on Nuevomexicanos - Gómez, Myrriah (Book collections on Project MUSE., 2022)
"Nuclear Nuevo Mexico: Identity, Ethnicity, and Resistance in Atomic Third Spaces is the study of the effects of the American nuclear program on Native American and Mexican-American communities in New Mexico. As the United States emerged as a nuclear leader following World War II, Los Alamos, New Mexico, became home to Site Y of the Manhattan Project-home of the atomic bomb. In the process of creating this nuclear technology, human and non-human life was destroyed. The experiences of Native American and Mexican-American communities have been neglected in the history of American nuclear technology. In this study Gómez seeks to show the local history of these two rural communities in New Mexico and how they were touched by the national discourse on the nuclear industrial complex from the spectrum of environmental racism and American exceptionalism. Gómez shows how some of these groups have resisted the mistreatment of their land and communities, while others have become complacent and have acquiesced to American nuclear development. The author incorporates the stories of Native American and Mexican American communities into the history of American nuclear technological development"--